PREVALENCE, TREATMENT AND CONTROL OF ASYMPTOMATIC HYPERURICAEMIA IN THE GENERAL CROATIAN POPULATION (EH UH 2 STUDY). (June 2022) - Bukal, Nikolina; Domislovic, Marija; Gellineo, Lana; Fucek, Mirjana; Begic, Zvonimir; Frkanec, Stjepan; Jelakovic, Ana; Radunovic, Danilo; Prelevic, Vladimir; Dika, Zivka; Karanovic, Sandra; Stevanovic, Ranko; et al.
Abstract : Objective: Hyperuricemia is acknowledged cardiovascular risk factor and determination of uric acid is a routine laboratory test in arterial hypertension. Debate is going on whether asymptomatic hyperuricemia should be treated or not, and what should be the targets. Our aim was to analyze prevalence of asymptomatic hyperuricemia, treatment and control in general Croatian population. Design and method: EHUH -2 study is nation-wide survey (Croatian Science Foundation) on hypertension and numerous cardiovascular risk factors in Croatia. In 2018–2021 a random sample of 1321 subjects were enrolled. Extended questionnaire was applied and subjects were clinically examined. Office blood pressure (BP) and heart rate were measured in sitting position using Omron 3 device three times and average BP values were calculated. Fasting blood sample was drawn after measurements and all lab data including uric acid were determined in a central laboratory. Hyperuricemia was defined as uric acid > 428 umol/l for men and > 357 umol/l for women Results: Prevalence of asymptomatic hyperuricemia was 12.6% without difference between men and women. Only 14.2 % of patients with asymptomatic hyperuricemia was treated with xanthine oxidase inhibitors. Normal values of uric acid were achieved in 71.5%. However, it means that in the entire group of patients with asymptomatic hyperuricemia only 10.1 % were under control. Conclusions: Prevalence of asymptomatic hyperuricemia is in line with reports from some countries (Italy 9–12%, Spain 5.11% and Sweden 10.16%), but lower than in North America, Russia, Japan and China. Small number of patients is treated and majority were not controlled. This therapeutic inertia should be improved by increasing awareness among physicians.